Estimating the Reliability Function for a Family of Exponentiated Distributions - Ajit Chaturvedi; Anupam Pathak (Journal of Probability and Statistics)
A family of exponentiated distributions is proposed. The problems of estimating the reliability function are considered. Uniformly minimum variance unbiased estimators and maximum likelihood estimators are derived. A comparative study of the two methods of estimation is done. Simulation study is preformed.